Analisis Kualitas Komunikasi Interpersonal Customer service dalam Meningkatkan Loyalitas Nasabah Bank PT. BPD Kaltim Kaltara Kantor Cabang Utama Samarinda - Putri, Nur Fadila Eka; Arsyad, Annisa Wahyuni; Dwivayani, Kadek Dristiana; Boer, Kheyene Molekandella (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
In Indonesia, the banking sector is expanding quickly, and rivalry among banks has become more intense. Customers have more options related to the increasing number of businesses in the same sector, thus the banking sector must offer the best service to increase customer loyalty. The Samarinda Central Branch Office of Bank PT BPD Kaltim Kaltara customer service attempts to provide customers with courtesy and friendliness by using interpersonal communication abilities. This research aims to analyze and describe how the quality of interpersonal communication used by customer service increases customer loyalty using the Social Exchange Theory and the Five Concepts of Interpersonal Communication which are Openness, Empathy, Support, Positiveness, and Equality. This research is qualitative research with a field research method, where data collection and results were obtained through interviews and direct observation of customer service and customers at the bank. The results of the research demonstrate that, despite certain challenges, such as instances of miscommunication between customers and customer service, the interpersonal communication standards for customer service have been carried out quite well. Customer loyalty and a favorable perception of Bankaltimtara are the results of customer service staff implementing five interpersonal communication concepts.